STEAM learning approach: realizing 21st century skills through increasing compound intelligence of class x students - Daniel Desianto Pasedan; Bernadetha Nadeak (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This classroom action research aims to improve students' multiple intelligences through the STEAM (Science, Technology, Engineering, Arts, and Math) learning approach in class X TKJ at SMK Kristen Tagari with 31 students as research subjects. The classroom action research consisted of three cycles and each cycle consisted of six actions. Collecting data using the method of observation, interviews, multiple intelligence tests, and documentation. The data analysis technique uses the average value and the percentage of multiple intelligence test results. The results showed an increase in all constructs of multiple intelligence in subjects as evidenced by the results of the average score of the first intelligence test 28.19, the second test 28.93, the third test 29.49 while the average percentage change in multiple intelligence scores on the first test to the second test amounted to 2.62%, the second test to the third test 1.96% and the first test to the third test of 4.62%. It is recommended for further research to conduct classroom action research using the STEAM learning approach, students' multiple intelligence tests by learning problems experienced in class.